2021
DOI: 10.12717/dr.2021.25.3.133
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activating Eel Luteinizing Hormone Receptors Induce Constitutively Signal Transduction and Inactivating Mutants Impair Biological Activity

Abstract: In contrast to the human lutropin receptor (hLHR) and rat LHR (rLHR), very few naturally occurring mutants in other mammalian species have been identified. The present study aimed to delineate the mechanism of signal transduction by three constitutively activating mutants (designated M410T, L469R, and D590Y) and two inactivating mutants (D383N and Y546F) of the eel LHR, known to be naturally occurring in human LHR transmembrane domains. The mutants were constructed and measured cyclic adenosine monophosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(57 reference statements)
0
3
0
1
Order By: Relevance
“…Our recent observations have suggested that activating or inactivating conformations of eel FSHR [ 3 ], equine FSHR [ 5 ], and equine LH/CGR [ 4 ] are significantly involved in the signal transduction of G proteins and the cell-surface loss of receptors by high-concentration agonist treatment. The N-linked glycosylation sites in the glycoprotein hormones are important for PKA signal transduction in the cells expressing these receptors [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent observations have suggested that activating or inactivating conformations of eel FSHR [ 3 ], equine FSHR [ 5 ], and equine LH/CGR [ 4 ] are significantly involved in the signal transduction of G proteins and the cell-surface loss of receptors by high-concentration agonist treatment. The N-linked glycosylation sites in the glycoprotein hormones are important for PKA signal transduction in the cells expressing these receptors [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have studied the GPCR signal transduction of activating and inactivating lutropin/chorionic gonadotropin receptors (LH/CG) and FSHRs, showing that the highly conserved regions in glycoprotein hormone receptors are similarly regulated in different species of both mammals and fish [ 3 , 4 , 5 ]. In recent years, we have been studying signal transduction in activating and inactivating mutants to characterize the specific function of the PKA pathway [ 17 ] and cell-surface loss of receptors [ 18 ] in eel LH/CGR. We found that the phosphorylation sites in the C-terminal region of equine LH/CGR are important for signal transduction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ген, що кодує рецептор лютеїнізуючого гормону/хоріогонадотропіну, розташований на хромосомі 2p21 людини, кодує трансмембранний рецептор, який експресується на клітинних мембранах тестикулярних клітин Лейдіга [18,24]. У чоловіків активація патогенних варіантів цього гена викликає надмірну секрецію тестостерону, що запускає раннє периферичне (передчасне) статеве дозрівання, тоді як гіперактивний рецептор не викликає клінічно значущих симптомів у дівчат [25,26].…”
Section: показникunclassified
“…Therefore, the C-terminal region of eLH/CGR has 14 potential phosphorylation sites and a highly conserved leucine motif that is essential for trafficking ( Duvernay et al, 2004 ; Byambaragchaa et al, 2021a , b , e ). The eCG, secreted from the placenta during early pregnancy, is a unique molecule that displays both LH- and FSH-like activities in non-equid species ( Min et al., 2019 , 2020 , 2021 ; Lee et al, 2021 ) and exhibits only LH-like activity in equine species ( Lee et al, 2017 , 2021 ; Park et al, 2017 ; Min et al, 2019 , 2020 ; Byambaragchaa et al, 2021c , d ).…”
Section: Introductionmentioning
confidence: 99%